Biomaterials in orthopaedic surgery - RodrÍguez-González, Federico Angel (ASM International, 2009)
Introduction to biomaterials in orthopaedic surgery - Structures of solids and phase diagrams. - Types of biomaterials in orthopaedics - Basic principles of biomechanics - Applications of materials testing - Selected applications of biomaterials in orthopaedic surgery - Bone allografts - Clinical cases - Failures modes of implants.